TLR3 stimulation induces melanosome endo/phagocytosis through RHOA and CDC42 in human epidermal keratinocyte. Issue 3 (December 2019) - Koike, Saaya; Yamasaki, Kenshi; Yamauchi, Takeshi; Shimada-Omori, Ryoko; Tsuchiyama, Kenichiro; Ando, Hideya; Aiba, Setsuya
Highlights: TLR3 agonist Poly(I:C) increases uptake of melanosome-rich globules, melanosomes, and melanocores by keratinocytes. Poly(I:C) increases protease-activated receptor-2 (PAR-2) expression. The knockdown of PAR-2 does not completely suppress endo/phagocytosis of melanin by Poly(I:C) stimuli. Poly(I:C) increases the expressions and activation of RHOA and CDC42. The knockdown of RHOA and CDC42 suppress endo/phagocytosis of melanin by Poly(I:C) stimuli. Abstract: Background: Keratinocytes and melanocytes in human epidermis express Toll-like receptors (TLR) and induce immune responses. We previously reported that TLR3 stimulation increases melanosome transport from perinuclear to cell membrane in melanocytes and enhanced release of melanosome from melanocytes, which were followed by increase in melanosome uptake into keratinocytes. Objective: In this study, we investigated whether TLR3 stimuli directly affect keratinocytes to enhance melanosome uptake. Methods: To observe keratinocyte's melanosome uptake ability precisely without melanocytes influences, we isolated melanosomes from human melanocytes and applied isolated melanosomes to keratinocytes stimulated by Poly(I:C). Results: Poly(I:C)-stimulated keratinocytes enhanced uptake of isolated melanosome-rich globules five-times as much as control. Poly(I:C) increases the RNA and protein expressions of RHOA and CDC42, which are small GTP-binding proteins inducing the endocytosis. Pull-down assay showed that Poly(I:C) increased the GTP-binding RHOA and CDC42, suggesting TLR3 stimulation activated RHOA and CDC42. The knockdown of TLR3 suppressed RHOA and CDC42 induction by Poly(I:C). Consistently, the knockdown of RHOA and CDC42 significantly suppressed the melanosome-rich globules uptake by Poly(I:C)-stimulated keratinocytes. Conclusion: Because RHOA and CDC42 activation induces endocytosis by modification of actin stress fiber and filopodia formation, respectively, these results suggested that TLR3 stimulation enhances melanosome uptake into keratinocytes through endocytosis mechanisms. Combining with the data of our previous publications, TLR3, which signal is activated by sensing viral molecules, enhance pigmentation by controlling both melanin transport system by RAB GTPases induction in melanocytes and uptake system by RHOA and CDC42 in keratinocytes.